Biologic and behavioral associations of estrogen receptor alpha positivity in head and neck squamous cell carcinoma. (October 2021) - Drake, Virginia; Bigelow, Elaine; Fakhry, Carole; Windon, Melina; Rooper, Lisa M.; Ha, Patrick; Miles, Brett; Gourin, Christine; Mandal, Rajarsi; Mydlarz, Wojciech; London, Nyall; Vosler, Peter S.; et al.
Highlights: Predictors of estrogen receptor alpha status in HNSCC are explored. Tumor HPV status and small tumor size were associated with ERα tumor expression. ERα may have a role in HNSCC tumor biology; further investigation as a prognostic biomarker is warranted. Abstract: Objectives: Tumor HPV status is an established independent prognostic marker for oropharynx cancer (OPC). Recent studies have reported that tumor estrogen receptor alpha (ERα) positivity is also associated with prognosis independent of HPV. Little is known about the biologic and behavioral predictors of ERα positivity in head and neck squamous cell cancer (HNSCC). We therefore explored this in a multicenter prospective cohort study. Materials and Methods: Participants with HNSCC completed a survey and provided a blood sample. Tumor samples were tested for ERα using immunohistochemistry. ERα positivity was defined as ≥1%, standardized by the American Society of Clinical Oncology/College of American Pathologists in breast cancer. Characteristics were compared with χ 2 and Fisher's exact test. Odds ratios (OR) were calculated using logistic regression. Results: Of 318 patients with HNSCC, one third had ERα positive tumors (36.2%, n = 115). Odds of ERα expression were significantly increased in those with HPV-positive tumors (OR = 27.5, 95% confidence interval[CI] 12.1–62), smaller tumors (≤T2, OR = 3.6, 95% CI 1.9–7.1), male sex (OR = 2.0, 95% CI 1.1–3.6), overweight/obesity (BMI ≥ 25, OR = 1.9, 95% CI 1.1–3.3), and those married/living with a partner (OR = 1.7, 95% CI 1.0–3.0). In a multivariate model, HPV-positivity (aOR = 27.5, 95% CI 11.4–66) and small tumor size (≤T2, aOR = 2.2, 95% CI 1.0–4.8) remained independently associated with ERα status. When restricted to OPC (n = 180), tumor HPV status (aOR = 17.1, 95% CI 2.1–137) and small tumor size (≤T2, aOR = 4.0 95% CI 1.4–11.3) remained independently associated with ERα expression. Conclusion: Tumor HPV status and small tumor size are independently associated with ERα expression in HNSCC.